Measuring the efficiency of outsourcing: an illustrative case study from the aerospace industry - Ferreira Filho, Angelo J. C. A.; Salomon, Valerio A. P. [UNESP]; Marins, Fernando A. S. [UNESP]; Loureiro, G.; Curran, R. (Springer, 2007)
Outsourcing is related to the action which an organization deals with its suppliers through a kind of business contract where a specific activity or service has been hired to be made. The outsourcing of some activities has become a common practice in the industry, nowadays. It reduces costs, significantly, in the production process and, at the same time, adds some values to the business organization. However it is necessary to measure the performance of these activities. Data Envelopment Analysis (DEA) is a non-parametric method useful to measure comparative performance. It has a wide range of applications measuring comparative efficiency. The Analytic Hierarchy Process (AHP) is a multiple criteria decision-making method that uses hierarchic structures to represent a decision problem and then develops priorities for the alternatives based on the decision-maker's judgments. This paper presents an integrated application based on DEA and AHP to evaluate the efficiency of subcontracted companies in a Brazilian aerospace factory.
Keywords: aerospace industry; efficiency and performance analysis; outsourcing; DEA; AHP